Novel role of Giα2 in cell migration: Downstream of PI3‐kinase–AKT and Rac1 in prostate cancer cells. Issue 1 (4th August 2018) - Caggia, Silvia; Chunduri, HimaBindu; Millena, Ana C.; Perkins, Jonathan N.; Venugopal, Smrruthi V.; Vo, BaoHan T.; Li, Chunliang; Tu, Yaping; Khan, Shafiq A.
Abstract : Tumor cell motility is the essential step in cancer metastasis. Previously, we showed that oxytocin and epidermal growth factor (EGF) effects on cell migration in prostate cancer cells require Giα2 protein. In the current study, we investigated the interactions among G‐protein coupled receptor (GPCR), Giα2, PI3‐kinase, and Rac1 activation in the induction of migratory and invasive behavior by diverse stimuli. Knockdown and knockout of endogenous Giα2 in PC3 cells resulted in attenuation of transforming growth factor β1 (TGFβ1), oxytocin, SDF‐1α, and EGF effects on cell migration and invasion. In addition, knockdown of Giα2 in E006AA cells attenuated cell migration and overexpression of Giα2 in LNCaP cells caused significant increase in basal and EGF‐stimulated cell migration. Pretreatment of PC3 cells with Pertussis toxin resulted in attenuation of TGFβ1‐ and oxytocin‐induced migratory behavior and PI3‐kinase activation without affecting EGF‐induced PI3‐kinase activation and cell migration. Basal‐ and EGF‐induced activation of Rac1 in PC3 and DU145 cells were not affected in cells after Giα2 knockdown. On the other hand, Giα2 knockdown abolished the migratory capability of PC3 cells overexpressing constitutively active Rac1. The knockdown or knockout of Giα2 resulted in impaired formation of lamellipodia at the leading edge of the migrating cells. We conclude that Giα2 protein acts at two different levels which are both dependent and independent of GPCR signaling to induce cell migration and invasion in prostate cancer cells and its action is downstream of PI3‐kinase–AKT–Rac1 axis. Abstract : We conclude that Giα2 protein acts at two different levels which are both dependent and independent of G‐protein coupled receptor signaling to induce cell migration and invasion in prostate cancer cells and its action is downstream of PI3‐kinase–AKT–Rac1 axis.